Anionic defects engineering of Co3O4 catalyst for toluene oxidation. (15th April 2022) - Bao, Liurui; Zhu, Shanhui; Chen, Yi; Wang, Yu; Meng, Wenhao; Xu, Shuai; Lin, Zehui; Li, Xingyun; Sun, Ming; Guo, Limin
Graphical abstract: Highlights: The anion defective Co3 O4 is successfully engineered by N doping. N doped Co3 O4 showed a toluene conversion rate 6.8 times that of pristine Co3 O4 . N doping could promote active oxygen generation and enhance the oxygen reactivity. Abstract: Development of advanced metal oxide catalysts for volatile organic compounds (VOCs) abatement is of great environmental and economic importance. Herein, a defective Co3 O4 catalyst is delineated via N doping. The anionic defects engineering significantly facilitated the oxygen vacancies formation, leading to a distorted lattice structure, increased active surface oxygen and enhanced oxygen mobility of Co3 O4 catalyst. These features promise an excellent toluene oxidation performance with 50% toluene conversion temperature (T50 ) of 208 °C and 90 % toluene conversion temperature (T90 ) of 218 °C at a space velocity of 60, 000 mL g −1 h −1, about 33 °C and 53 °C lower than that of the pristine Co3 O4, respectively. Meanwhile, the N doped Co3 O4 catalyst maintains a high hydrothermal stability at 210 °C. This work exemplifies the significance of anionic defects for the intrinsic catalytic oxidation ability improvement, providing a guidance for the upgradation of the metal oxide for the application of VOCs catalytic degradation and beyond.